2021
DOI: 10.1038/s41598-020-79539-w
|View full text |Cite
|
Sign up to set email alerts
|

Histone acetyltransferase PfGCN5 regulates stress responsive and artemisinin resistance related genes in Plasmodium falciparum

Abstract: Plasmodium falciparum has evolved resistance to almost all front-line drugs including artemisinin, which threatens malaria control and elimination strategies. Oxidative stress and protein damage responses have emerged as key players in the generation of artemisinin resistance. In this study, we show that PfGCN5, a histone acetyltransferase, binds to the stress-responsive genes in a poised state and regulates their expression under stress conditions. Furthermore, we show that upon artemisinin exposure, genome-w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 63 publications
0
23
0
Order By: Relevance
“…Recently, it was shown that parasites that carry a deletion of the bromodomain of the histone acetyltransferase PfGCN5, lose the mutually exclusive expression of the var genes and upregulate multiple var genes in a single cell at the same time, implicating PfGCN5 in var gene silencing ( Miao et al, 2021 ). Consistent with a direct association with VSA genes, PfGCN5 was also mapped by ChIPseq to the heterochromatic compartment in trophozoites, providing another example of a heterochromatin associated P. falciparum bromodomain protein ( Rawat et al, 2021 ). Interestingly, PfGCN5 KO also showed a similar phenotype as PfBDP1 depletion regarding invasion gene regulation, thus functionally linking the two bromodomain complexes with each other ( Miao et al, 2021 ).…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Recently, it was shown that parasites that carry a deletion of the bromodomain of the histone acetyltransferase PfGCN5, lose the mutually exclusive expression of the var genes and upregulate multiple var genes in a single cell at the same time, implicating PfGCN5 in var gene silencing ( Miao et al, 2021 ). Consistent with a direct association with VSA genes, PfGCN5 was also mapped by ChIPseq to the heterochromatic compartment in trophozoites, providing another example of a heterochromatin associated P. falciparum bromodomain protein ( Rawat et al, 2021 ). Interestingly, PfGCN5 KO also showed a similar phenotype as PfBDP1 depletion regarding invasion gene regulation, thus functionally linking the two bromodomain complexes with each other ( Miao et al, 2021 ).…”
Section: Discussionmentioning
confidence: 59%
“…Bromodomain proteins bind to acetylated lysine residues on histones and interact with specific transcription factors to recruit the chromatin remodeling and transcriptional machineries ( Josling et al, 2012 ; Fujisawa and Filippakopoulos, 2017 ). In P. falciparum , eight bromodomain proteins have been predicted [PfBDP1-4, PfTAF1 (PfBDP5), PfTAF2 (PfBDP6), PfSET1 and PfGCN5 ( Nguyen et al, 2020 )], of which only PfBDP1 and the histone acetyltransferase PfGCN5 have been functionally characterized ( Cui et al, 2007 ; Josling et al, 2015 ; Bhowmick et al, 2020 ; Rawat et al, 2020 ; Miao et al, 2021 ; Rawat et al, 2021 ). PfBDP1 is an essential protein that binds to acetylated histones notably in actively transcribed gene promoter regions ( Josling et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…This makes the functions of homeostatic chaperone protein even more important in parasite survival. The chaperone proteins and the protein homeostasis-associated machinery are reported to be extensively involved in emergence of artemisinin resistance and thus interesting molecular candidates to follow ( Rawat et al, 2021 ). The T-complex 1 subunit beta (PF3D7_0306800) and subunit delta (PF3D7_1357800), putative chaperone binding protein (PF3D7_1334200), prefoldin subunit 6 (PF3D7_0512000), and DnaJ protein (PF3D7_0523400), Hsp101 (PF3D7_1116800; ClpB2), and prefoldin subunit 2 (PF3D7_1416900) were upregulated in artemisinin-resistant parasites ( Supplementary Table S5 ).…”
Section: Resultsmentioning
confidence: 99%
“…The transcriptional profiles unique to resistant parasites are believed to be overlaid on a complex interaction of environmental pressures and selective evolution of genotypes ( Mok et al, 2011 ; Dwivedi et al, 2017 ). Epigenetic factors that can respond to environmental perturbations in real time and evoke rapid responses in parasites may also contribute to resistance as shown in a recent study ( Rawat et al, 2021 ). Identifying the markers and mechanisms of resistance in K13-independent resistance is also the next challenge and comparative multiomics can bolster investigations into these questions.…”
Section: Introductionmentioning
confidence: 89%
“…Further study of PfGCN5 bromodomain deletion mutants revealed growth defects that were associated with dysregulation of gene expression and modified chromatin states due to the reduction in histone acetylation, leading to altered cellular pathways [ 15 ]. RNA-seq and ChIP-seq analyses found that PfGCN5 is significantly up-regulated under stress conditions and binds to the promoter region of stress-responsive genes, respectively [ 16 ]. This suggests that PfGCN5 drives the parasite stress response by placement and recognition of acetylated lysine residues but is not required for parasite survival.…”
Section: Introductionmentioning
confidence: 99%